Hydrogel-based formulations for urothelial cancer therapy - Chang, Mingyang; Chi, Changliang; Zheng, Zuozhu; Zhang, Ming; Lv, Jianing; Wang, Xiaoqing (Frontiers in Pharmacology, 2024)
Drug infusion therapy after surgery for urothelial carcinoma is an effective measure to reduce cancer recurrence rate. Hydrogels are drug carriers with good biocompatibility and high drug loading capacity, which can optimize the pharmacokinetics of drugs in the urinary system to improve the therapeutic effect. Compared with the traditional free drug in situ perfusion, the hydrogel drug loading system can still maintain effective drug concentration in the face of continuous urinary flushing due to its good mucosal adhesion effect. The significantly prolonged drug retention time can not only improve the therapeutic effect of drugs, but also reduce the discomfort and risk of urinary tract infections caused by frequent drug infusion, and improve patient compliance. In addition, the combination of hydrogel with nanoparticles and magnetic materials can also improve the mucosal permeability and targeting effect of the hydrogel drug loading system, so as to overcome the mucus layer of urinary epithelium and the physiological barrier of tumor and minimize the impact on normal tissue and cell functions. At present, the research of hydrogels for urothelial cancer treatment involves chemotherapy, immunotherapy, gene therapy, inhibition of metabolism and multi strategy synergistic therapy. This review summarizes the research progress of hydrogels for the treatment of urothelial carcinoma, hoping to provide a reference for the future research of safe, reliable, effective, and advanced hydrogels with little side effects.